Effect of Vagus Nerve Stimulation in Vestibular Function among Subjects with Stroke. - Sharmila R.; Srinivasan, Vignesh; Suganthirababu, Prathap; Kumar, Priyadharshini; Dhanusia S.; Kumaresan A.; Vishnuram, Surya (Indian Journal of Physiotherapy & Occupational Therapy)
Background: The background of the study is the incidence of vestibular dysfunction among stroke subjects which indirectly affects the balance function and early recovery of daily activities like sitting, standing and walking. Purpose: The main objective of this study is to investigate the vestibular dysfunction using Vestibular evoked myogenic potential (VEMP) and efficiency of Transcutaneous auricular vagal nerve (TaVNS) stimulation among Middle cerebral artery (MCA) stroke survivors. Method: Thirty subjects were randomly assigned into one of two groups: Group A (Transcutaneous auricular vagal nerve stimulation with conventional stroke rehabilitation) and Group B (conventional stroke rehabilitation and epley's maneuver). The pre-test measures of vestibular function were assessed by VEMP (an electrophysiological diagnostic tool). The intervention group received Transcutaneous auricular vagal nerve stimulation for 30 minutes, and a single session per day for 4 weeks along with conventional stroke rehabilitation whereas the control group received Epley's maneuver exercises along with conventional stroke rehabilitative exercises for 60 minutes, 6 days/week, and a single session per day for 4 weeks. The same VEMP test was measured after 4 weeks of treatment as post-test values. Result: The pre and post-test values were significantly different between group A and group B (p ≥ 0.001) indicating that TaVNS has a major impact on recovery of vestibular dysfunction among stroke participants. Conclusion: The transcutaneous auricular vagal nerve stimulation is found effective for improving the vestibular function and balance.